Depressive disorders in medical students under chronic stress - Dzeruzhynska Наталія; Hyndych Анна (Psychosomatic Medicine and General Practice, 2024)
Relevance. Chronic stress causes a prolonged adaptive response to significant traumatic events. The psychological situation in modern Ukraine is characterized by the massive impact of a number of such events. A natural response to this is the development of mental, including affective, disorders. Many researchers have studied the impact of such events on young people, including students. It has been found that medical students in peacetime demonstrate high rates of depressive spectrum disorders, especially among younger age groups. The wide prevalence of depressive disorders in medical students, the combination of forms of stressful events and their duration in our conditions, and the lack of practical recommendations for the provision of psychological and psychiatric care to such individuals determine the relevance of this study. Objective. To create a set of recommendations for increasing stress resistance and improving the mental state of medical students by identifying symptoms of emotional disorders and determining the factors that have the greatest impact on the mental state and quality of life. Materials and methods. The study was conducted by conducting an online survey using Google Forms among 122 students of different courses at a medical university (without signs of mental disorders in their anamnesis). Of these, 48 were male and 74 were female, aged 17 to 23. The questionnaire was created with questions that included complaints, self-assessment of health and study regimen, social indicators (whether they left their home during the war, whether they had COVID-19, the relationship of these factors to their condition, etc.), and the means used to overcome emotional problems. To assess the level of depressive symptoms, a health questionnaire (PHQ-9) was used. Results and discussion. Almost all students reported changes in their emotional state of varying duration and severity. The use of the health questionnaire (PHQ-9) revealed that only 22 (18.0%) students had no depressive symptoms. The distribution of the severity of depressive symptoms was as follows: mild - 29 (23.8%) people, moderate - 35 (28.7%) people, moderately severe - 25 (20.5%) people and severe - 11 (9.0%) people. The proportion of more severe depressive manifestations was found among senior students. A direct moderate correlation was found between the severity of depressive manifestations and changes in the academic performance of medical students (r=0.338 at p=0.000139) and satisfaction with interpersonal relationships (r=0.413 at p=0.000002). Conclusion. Medical students demonstrated high rates of depressive spectrum disorders. The most pronounced levels of these disorders were observed in senior students. Recommendations are proposed to increase students’ stress resistance and improve their emotional well-being. The study indicates a high need to create psychoeducational programs for this contingent of people with their implementation in the curriculum in order to support emotional well-being and prevent the occurrence of emotional disorders and burnout in future doctors.